2017
DOI: 10.18203/2320-6012.ijrms20171873
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome in a rural population- a cross sectional study from Western Uttar Pradesh, India

Abstract: Background: Prevalence of non-communicable diseases like hypertension, diabetes mellitus and coronary artery disease is on the rise due to the change in lifestyle, unfavourable dietary habits and obesity. Metabolic syndrome is a simple tool by which we can predict the future risk of diabetes mellitus and cardiovascular disease. Studies showed that prevalence of metabolic syndrome is rising in Indian population, but majority of them were done in urban population. This study was conducted to look into the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 8 publications
2
19
1
Order By: Relevance
“…The prevalence of MS in college students was 5.3% (6.5% men and 4.1% women). The prevalence rate of students with MS in this study was higher than that mentioned in some studies [2,7,10,11] and lower than that mentioned in others [19,20,21]. These data show that the proportion of college students with MS in Korea is higher than that in Western countries.…”
Section: Discussioncontrasting
confidence: 68%
“…The prevalence of MS in college students was 5.3% (6.5% men and 4.1% women). The prevalence rate of students with MS in this study was higher than that mentioned in some studies [2,7,10,11] and lower than that mentioned in others [19,20,21]. These data show that the proportion of college students with MS in Korea is higher than that in Western countries.…”
Section: Discussioncontrasting
confidence: 68%
“…NCEP-ATP III and IDF, half of the study participants with metabolic syndrome (50% and 45.91% respectively) are in the older age group of 51-70 years. These observations are going well with the results of Zafar et al, 10 and Kamble et al, 24 , which showed a higher prevalence of metabolic syndrome in the population above 50 years of age. The trend as in our study shows an increase in central obesity, one of the important components of metabolic syndrome by IDF criteria is comparable to other studies, which shows a similar trend 11 .…”
Section: Discussionsupporting
confidence: 92%
“…Cameron et al, 5 have reasoned that the differences in genetic background, diet, amounts of physical activity, 7 states that one-third of the urban population in India's major cities have metabolic syndrome. The prevalence of metabolic syndrome in Indian adults is ranged from 11% to 56% as reported by Sinha et al 8 There are many studies reporting the prevalence of metabolic syndrome in Indian populations 9,10,11,12,13 , reporting the increasing prevalence but till date this (Jammu) geographical part of India has never been covered by government as well as by any epidemiologist. Therefore, keeping in mind the present status, the study was conducted in Udhampur, Jammu city with the aim to study the prevalence of metabolic syndrome.…”
mentioning
confidence: 99%
“…In this prospective, case control study, women clinically diagnosed with PCOS (N=100) and age matched healthy control female subjects (N=100) in the age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) years were enrolled & conducted in the department of Obstetrics and Gynecology; SGT medical college, Hospital and Research Institute (SGT University) Gurugram-Delhi-NCR, India. The study was approved by Institutional Ethical Committee.…”
Section: Methodsmentioning
confidence: 99%
“…28 However PCOS may intensify the adverse effects of obesity on insulin resistance. 29 On the other hand recent research by Zafar KS et al 30 suggested that not all women with PCOS will develop dyslipidaemia and its complications but having PCOS enhances the chance for it Decreased HDL-C has been reported in more than two -thirds of PCOS subjects. 31 Our study has shown an increased level of FBS in PCOS patients indicating abnormal glucose metabolism similar to Rabelo -Acevedo M et al 32 Deranged lipid profile in PCOS women and significant positive correlations of lipid profile with BMI and WHR has also been shown recently by Shah et al 23 but this is contradictory to what has been reported by Kalra et al 27 who did not find any such correlation.…”
Section: Dyslipidaemia With Pcosmentioning
confidence: 99%